Aroma Composition and Sensory Quality of Cabernet Sauvignon Wines Fermented by Indigenous Saccharomyces cerevisiae Strains in the Eastern Base of the Helan Mountain, China. Issue 11 (1st November 2016) - Liu, Ning; Qin, Yi; Song, Yu-Yang; Tao, Yong-Sheng; Sun, Yue; Liu, Yan-Lin
Abstract : In order to improve the regional flavor peculiarity of Cabernet Sauvignon wine in the eastern base of the Helan Mountain, an Appellation of Origin in China, eight indigenous Saccharomyces cerevisiae strains were studied and evaluated. Compared to commercial control F15, indigenous N11424 present significant difference in the concentration of hexyl acetate, isoamyl acetate, ethyl hexanoate, diethyl succinate, and methyl benzoate, and the highest content of esters and least of alcohols were found in the wine made by N11424. By sensory analysis, N11424 wine was characterized with honey, pepper, as well as more fruit flavor, such as peach, cherry, clove, redcurrant, and blackcurrant. By odor activity value analysis, most of the high impact odorants were esters and the odor activity values of esters in most of indigenous strains were higher than in control F15.